Legal Analysis of Criminal Sanctions for Illegal Abortion Perpetrators under the Health Law Perspective - B.Prabowo; D.Ramadhan (The Medical Journal of Hospital Management and Health Law, 2025)
Introduction: Illegal abortion remains a critical medico-legal issue in developing nations, where the tension between criminal law enforcement and reproductive health rights creates complex statutory ambiguities. This study examines the legal framework governing criminal sanctions for illegal abortion perpetrators, focusing on how health legislation balances punitive measures with public health considerations. Methods: This study utilizes a normative legal research methodology, employing statutory, conceptual, and comparative approaches to analyze secondary legal sources, including the Indonesian Penal Code, health statutes, and related medical-legal jurisprudences. Results: The analysis reveals that while state legislation strictly criminalizes unauthorized pregnancy terminations to protect potential human life, current health statutes provide specific, highly regulated exemptions for medical emergencies and rape survivors. However, ambiguities in procedural execution and delayed legal determinations often inadvertently push individuals toward unsafe, clandestine practices. Discussion: The discussion evaluates the intersection of criminal law deterrence and public health realities, highlighting a significant research gap in the operational sync between law enforcement and medical professionals. By reviewing extensive literature on medical jurisprudence, this section emphasizes that rigid punitive measures without clear clinical guidelines fail to reduce abortion rates, instead increasing maternal mortality and exacerbating systemic health risks. Conclusions: This study concludes that legislative reform must shift from an exclusively punitive paradigm to an integrated regulatory framework that provides clear legal certainty, streamlined clinical protocols, and robust protection for healthcare providers.